Perioperative Complications of Video-Assisted Thoracoscopic Pulmonary Procedures in Neonates and Infants - Zoeller, Christoph; Ure, Benno M.; Dingemann, Jens (European Journal of Pediatric Surgery, 2018)
Video-assisted thoracoscopic surgery (VATS) has gained broad acceptance among pediatric surgeons. Today, VATS can be regarded as a routine approach for various conditions in neonates and infants. However, there is a lack of information concerning the complications of thoracoscopic pulmonary surgery in neonates and infants. We aimed to review the available data. A systematic review of the literature was performed using PubMed. All publications reporting on VATS for pulmonary procedures in neonates and infants up to the age of 1 year were included. Articles were reviewed in detail for occurrence of perioperative complications and their treatment. Nine case series were eligible for analysis. Entities treated included lung sequestration, congenital pulmonary airway malformation, congenital lobar emphysema, and bronchogenic cyst. Case series reported on a total number of 135 patients. Complications occurred in 14 patients (10.4%). The major complication was an accidental transection of the middle lobar bronchus that concluded in a later resection of a prior unaffected lung lobe. Other relevant complications reported were bleeding in four patients (3.0%) and persistent air leak in four cases (3.0%). Infectious complications were reported in four patients (3.0%). Additionally, iatrogenic phrenic nerve paralysis occurred in one patient. There were no deaths related to the VATS technique. In 11 cases (8.1%), conversion to thoracotomy had been necessary. General recommendations on the treatment of complications could not be derived due to small patient numbers and lack of details of the complications reported. Reports on major complications of pulmonary VATS in neonates and infants below 1 year of age are scarce. As severe complications such as accidental bronchus transection have been described, feasibility of neonatal/infant VATS cannot be unequivocally confirmed. No literature-based recommendation can be given on the treatment of complications.
Keywords: VATS; complications; pulmonary surgery; thoracoscopy; neonates and infants